From Existential Psychotherapy to Existential Medicine (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
The aim of this article is to emphasise the relevance of existential analysis not just to psychotherapy but to both the philosophy and practice of medicine. Its message is that the very division of 'psychotherapy' from 'somatic' medicine runs counter to the philosophical foundations of existential analysis.
Keywords: Psychotherapy; somatic medicine; biomedicine; iatrogenesis; felt body; felt dis-ease; meaning of illness; Zollikon seminars